Development of Si Beam Position Detectors for NA61/SHINE experiment. (December 2020) - Makhnev, A; Guber, F; Serebryakov, D; Pulawski, S; Kowalski, S
Abstract: The NA61/SHINE experiment at the CERN SPS is undergoing a major upgrade during the LHC Long Shutdown 2 period (2019-2021). The upgrade is essential to fulfil the requirements of the new open charm measurement program. In this program detector will operate at a beam intensity increased by a factor of 10, which requires an upgrade of current Beam Position Detectors (BPDs). New BPDs should monitor lead and proton beam intensities with up to 10 5 Hz rate. In this paper, progress on design and development of the new BPDs based on Si strip detectors, its front-end and readout electronics, as well as integration with the NA61/SHINE DAQ is presented.